Evaluation of Drought Tolerance Indices for Screening Some of Super Sweet Maize (Zea mays L. var. saccharata) Inbred Lines - Mohsen Shahrokhi; Saeed Khavari Khorasani; Asa Ebrahimi (AGRIVITA, Journal of Agricultural Science, 2020)
Drought is the most common cause of severe crop production shortage in developing countries, and global warming is predicted to further exacerbate drought’s impact. The present study investigates the efficiency of drought tolerance indices in classifying 24 super sweet maize inbred lines with the highest yield potential and drought tolerance performance. The experiment was conducted as a completely randomized block design with 4 replications. Twenty indices were compared based on grain yield, under two environments (Non-Stressed and Drought-Stress condition) during the 2018 growing season. All drought indices revealed significant differences among inbred lines, except GM. Results in ranking method, indicate that STI, GMP, MP, HARM, MRP, REI and RDY are suitable indicators because of positive correlations among each other and also the highest correlation with grain yield (GY) in both environments. Cluster analysis and threedimensional plots, showed inbred lines with the highest tolerance to drought, in both conditions. The first three principle components (PCs) explained 96.34% of total variation and the PC1 can be nominated as a potentially stable yield. The Biplot diagram based on PCs, and drought tolerance indices showed that MP, GMP, STI, HARM, MRP, REI, MSTIK1, MSTIK2 and YI were the best indices for screening tolerant inbred lines such as MCH87002/19-1, MPA90010/51-1 and MSH90011/82-1.